(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
Sesame is one of the most important oilseed crops in the tropical and subtropical regions of the world. Despite its importance, sesame yield in Nigeria is poor due to lack of improved and high yielding varieties. The aim of the work was to study genetic diversity in some agro-morphological traits of sesame germplasm. Germplasm exploration was carried out using systematic survey from October 2022 to September 2023 in different sites across Nasasrawa State. One hundred and twenty (122) germplasm was collected and evaluated in an incomplete randomized block design with 3 replications at the Faculty of Agriculture, Federal University Lafia, during October 2023 under irrigation. Data was collected on plant height (cm), number of primary branches (NBR), number of Capsules per plant and seed yield per plant (g), Analysis of variance revealed significant (p < 0.01) variation among the 122 genotypes for all the traits studied. Partitioning the significant variations into variance components showed that genotypic variance range from 0.92 for SYP to 287.34 for PHT. The genotypic effects have significant contribution to the phenotypic variation in all traits. The magnitude of the genotypic variance component resulted in high heritability estimates for PHT and CAP. Biplot PCA on agro-morphological traits displayed three principal components that contributed for 71.38% variations. Cluster analysis grouped the collected germplasm into three main clusters. The phenotypic diversity observed in this study may be exploited in the selection of parental lines for hybridization when breeding sesame for high seed yield